O fim do fator previdenciário e a introduç\~ao da idade mínima: Quest\~oes para previdência social no Brasil - Marcelo Abi-Ramia Caetano; Leonardo Alves Rangel; Eduardo da Silva Pereira; Graziela Ansiliero; Luis Henrique Paiva; Rogério Nagamine Costanzi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The objectives of this paper are i) to assess the recent changes in the "actuarial factor" and their distributive and financial impacts in the short and long term. The actuarial factor was created in 1999 to adjust the individual benefit level according to age, time of contribution and life expectancy at the time benefit is granted and was made optional by Law 13.183/2015; ii) to present the rules of old age pensions in Brazil, from a comparative perspective; and iii) to assess scenarios for pension reforms in Brazil, considering the introduction of a minimum wage rule.Law 13.318/2015 will increase social security expenditures in the long term (as compared to the previous scenario) and make these expenditures more regressive, increasing individual and regional economic inequalities in Brazil. As projections for the basic scenario already suggest a strong increase in social security expenditures, any additional increase is a reason for concern. Projections for the basic scenario are influenced by rules for old age pensions in Brazil, that do not follow the international best practices and that are adopted in only 13 other countries (among the 177 whose regulations are compiled by the International Social Security Association).Projections for the demographic evolution over the next decades point to a challenging scenario regarding the social security management in Brazil. By 2060, the country will have two working-age people for each person aged 65 or more. Adopting a minimum age threshold of 65/60 years for men/women, respectively, to have access to old age pensions will only marginally improve the trajectory of social security expenditures in the long term - suggesting that other reforms will be necessary.
Keywords: H53; H55; J11; 330; length of contribution pension; actuarial factor; pension reform; demography and public policies; pension expenditure forecast